Development and Stability Assessment of Guava-Moringa Sauce with Nutritional, Microbial and Physicochemical Analysis - Noor, Aimen; Shaukat, Amal; Mustafa, Fahad; Rasheed, Muhammad Ehtisham; Nawaz, Shaista; Usama, Muhammad; Ahmad, Ammar; Batool, Saira (Biological and Clinical Sciences Research Journal, 2025)
Moringa (Moringa oleifera), belonging to the Moringaceae family, is a nutrient-dense plant rich in essential phytochemicals that effectively combat malnutrition. Similarly, guava (Psidium guajava L.), often termed the “Apple of the Tropics,” is recognized for its year-round production, affordability, and high nutritional value. The combination of guava and moringa presents an innovative approach to developing a functional food product with enhanced nutritional and sensory attributes. Objective: This study aimed to develop and characterize guava–moringa sauce and to evaluate its shelf stability by analyzing its nutritional, microbial, physicochemical, and sensory properties. Methods: A laboratory-based experimental study was carried out from February to July 2025. Four treatment formulations were prepared: T₀ (100% guava), T₁ (98% guava + 2% moringa), T₂ (96% guava + 4% moringa), and T₃ (94% guava + 6% moringa). The sauce was prepared following the procedure of Ritthiruangdej et al. (2011) with slight modifications. Physicochemical parameters including moisture, ash, fat, crude fiber, crude protein, and color were analyzed on days 0, 7, and 14. Color was determined using a handheld spectrocolorimeter (Lovibond LC-400), and viscosity was measured using a BDV-8S viscometer (No.18DN3270, Shandong Co., Ltd). Microbial stability was assessed through bacterial and mold counts, while sensory evaluation was performed by a trained panel of 10 members using a 9-point hedonic scale. Data were analyzed with Statistix 8.1, and results were considered significant at p < 0.05. Results: The addition of moringa significantly enhanced the crude fiber content in T₂ and T₃ compared with the control (T₀). T₃ exhibited the highest fiber content but had slightly lower sensory scores for taste and texture. T₂ and T₃ demonstrated the most favorable balance between enhanced nutritional quality and acceptable sensory attributes. Throughout the 14-day storage, all formulations remained microbiologically safe. However, T₂ maintained better moisture and texture stability, while T₃ exhibited improved sensory parameters including color and consistency, though with minor flavor alterations as moringa concentration increased. Conclusion: Incorporation of moringa leaves, particularly at 4–6% concentration, improved the nutritional profile and shelf stability of guava-based sauces without compromising sensory acceptability. T₃ showed superior overall sensory quality, including texture, flavor, aroma, and color, suggesting that moringa can serve as a natural stabilizer and functional additive in plant-based sauces, offering both nutritional and gastronomic benefits.